2001
DOI: 10.1029/2001jd000345
|View full text |Cite
|
Sign up to set email alerts
|

Impact of 837 GPS/MET bending angle profiles on assimilation and forecasts for the period June 20–30, 1995

Abstract: Abstract. With a ray-tracing procedure and variational data assimilation techniques, it is now possible to make direct use of radio occultation bending angles, rather than their derived temperature and moisture retrievals, in atmospheric data analysis and assimilation. This paper describes results obtained from including more than 800 GPS/MET bending angle profiles, available over an l 1-day period, 20-30 June 1995, into the National Centers for Environmental Prediction spectral statistical interpolation analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 16 publications
0
39
0
Order By: Relevance
“…However, when this is not feasible, the assimilation of refractivity profiles is superior to the assimilation of temperature and humidity profiles derived from the RO measurements. Positive results from assimilation experiments with bending angle profiles from the GPS/MET and CHAMP missions have been presented by Liu et al (2001) and Zou et al (2004), but these studies did not assimilate all the other satellite measurements that were available at that time. Healy et al (2005) has demonstrated a positive impact on stratospheric temperatures in a 16-day trial with the assimilation of CHAMP refractivity profiles into the operational Met Office 3DVAR system.…”
Section: Or Infrared Sounders (Collard and Healy 2003)mentioning
confidence: 98%
“…However, when this is not feasible, the assimilation of refractivity profiles is superior to the assimilation of temperature and humidity profiles derived from the RO measurements. Positive results from assimilation experiments with bending angle profiles from the GPS/MET and CHAMP missions have been presented by Liu et al (2001) and Zou et al (2004), but these studies did not assimilate all the other satellite measurements that were available at that time. Healy et al (2005) has demonstrated a positive impact on stratospheric temperatures in a 16-day trial with the assimilation of CHAMP refractivity profiles into the operational Met Office 3DVAR system.…”
Section: Or Infrared Sounders (Collard and Healy 2003)mentioning
confidence: 98%
“…Liu et al, 2001;Healy et al, 2005), GPSRO data available in near real time has not previously been operationally assimilated into NWP models. Following previous 3D-VAR data assimilation experiments at the Met Office (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…All of these approaches have been investigated in recent forecast impact experiments. To briefly summarize, Liu et al (2001) presented results from an 11-day trial assimilating GPS/MET bending-angle profiles using a ray-tracing forward model in a threedimensional variational (3D-Var) system. Although they claimed a small but consistent improvement in the forecast scores, the results were limited because other satellite data available at that time were not assimilated.…”
Section: Introductionmentioning
confidence: 99%